Metode Pembinaan Akhlak Mahasantri Ma'had Al-Jami'ah IAIN Kendari - Wa Ode Hardiana; Fatirawahidah (Yayasan Ishlahul Muslimin Konawe Selatan, 2025)
The goal of this study is to determine the best ways for fostering moral development in Ma'had al-Jami'ah IAIN Kendari students as well as the elements that might either impede or encourage this development. This kind of study uses field observations, interviews, and documentation to gather data. It is descriptive qualitative and takes a phenomenological approach. Regarding the analysis, the author employs descriptive analysis, which seeks to clarify the traits and facets that are pertinent to the occurrences that occur. The study's findings demonstrated that the administrators employed a variety of strategies to promote Ma'had mahasantri morality, including the employment of role models, habit formation, advice-giving techniques, parables, and incentives and penalties. Furthermore, environmental elements, human resources (HR), working with other parties, and ma'had facilities are supportive aspects in the development of student morality. The next barrier to moral development is the majority of public school graduates' educational background in non-Islamic boarding schools, followed by students' lack of motivation to change for the better, as evidenced by the fact that they frequently engage in illegal behavior like skipping class or other activities. Finally, the researcher advises students living at Ma'had Al-Jami'ah IAIN Kendari that the moral development practiced in the dormitory, whether through exemplary methods, habituation, giving advice, parables, awarding rewards, and punishing infractions, aims to inform students about the significance of moral development.